The European Commission of the Danube, 1856-1948 An Experiment in International Administration - Ardeleanu, Constantin (Balkan Studies Library, 2020)
The history of the world's second international organisation, an innovative techno-political institution established by Europe's Concert of Powers to remove insecurity from the Lower Danube.; Readership: Historians of nineteenth and twentieth centuries European history, scholars and students in the history of international relations, international organisations, science and technology studies. Keywords: Danube, Danube Delta, Sulina, Romania, Southeastern Europe, Danube Commission, international organizations, international relations, 1856-1940, river histories, technopolitics, internationalism, navigation.